Across Anthropology Troubling Colonial Legacies, Museums, and the Curatorial - von Oswald, Margareta; Tinius, Jonas (Leuven University Press, 2020)
"How can we rethink anthropology beyond itself? In this book, twenty-one artists, anthropologists, and curators grapple with how anthropology has been formulated, thought, and practised 'elsewhere' and 'otherwise'. They do so by unfolding ethnographic case studies from Belgium, France, Germany, Italy, the Netherlands, and Poland - and through conversations that expand these geographies and genealogies of contemporary exhibition-making. This collection considers where and how anthropology is troubled, mobilised, and rendered meaningful. Across Anthropology charts new ground by analysing the convergences of museums, curatorial practice, and Europe's reckoning with its colonial legacies. Situated amid resurgent debates on nationalism and identity politics, this book addresses scholars and practitioners in fields spanning the arts, social sciences, humanities, and curatorial studies. "